Urban Megaprojects: How they are justified and who they benefit. The case of Century City - Kamalie, Mariam (University of Cape Town, 2020)
All over the world, megaprojects have become entrenched and firmly positioned in the development of cities and have become instrumental and critical in their position and functioning. The need for sites to be developed encompassing mixed-use requirements, was soon to make its impact in developing countries. Investors and developers were considered the experts in urban development through these projects. The now notable effects from the surge in megaprojects in developing countries in the wake of decaying infrastructure and migration to cities and urban spaces, warrants analysing, studying and investigating existing, especially more current mixed-use megaprojects. Megaprojects built with the motivation of the criteria for "enhancing and developing" the urban space for its citizens that encourages economic, social and environmental growth would be alluring to any governing administration. This is because they can be considered as developments that will address the spatial patterns of apartheid, creating inclusive and integrated urban spaces. Considering these impacts, Century City, as a commercial mixed-use mega project development is a relevant case for study. My dissertation analyses and interrogates the factors that influenced and substantiated the development of Century City from its inception to the present. I will examine how the development coexists, and complements or not, Cape Town and its people and how it may or may not support the policy approaches toward a successful African city. I question whether megaproject developments in our cities, is development that transmits to the entire city and its community.